Concept of a Molecular Charge Storage Dielectric Layer For Organic Thin-Film Memory Transistors - Burkhardt, Martin; Jedaa, Abdesselam; Novak, Michael; Ebel, Alexander; Voitchovsky, Kislon; Stellacci, Francesco; Hirsch, Andreas; Halik, Marcus (Advanced Materials, 2010)
(Figure Presented) A mixed self-assembled monolayer containing aliphatic and electron-accepting (C ) components is employed as an ultrathin molecular gate dielectric to facilitate reversible, nonvolatile electronic memory functionality in organic transistors at low supply voltages. By adjusting the stoichiometry of the monolayer components, the transistor and memory characteristics can be tuned. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.